Comparative Corporate Governance Shareholders as a Rule-maker - Mäntysaari, Petri (Springer Berlin Heidelberg : Imprint: Springer, 2005)
It is fairly easy for a Finnish Jurist to understand German Company law. On the other hand, UK Company law seems very confusing. What is even more confusing is that the UK corporate govemance model is often regarded as one of the best in the World. Clearly German law cannot be as bad as it is often said to be. This books results from these kinds of thoughts and an interest in comparative law, Company law and securities markets law. I wanted to find out whether the functional method would give anything new to say about the regulation of corpo rate govemance in Germany and the UK. As I have been lecturing on Company law and corporate govemance myself, I also wanted to write a book that I could use as a textbook in my courses. For this reason, I focused on one of the key questions in corporate govemance: the regula tion of shareholder activism.